Sharia Capital Market as an Investment Instrument for Indonesia’s Economic Development - Herawati, Popi (Islamicate Institute, 2019)
This study investigates the Sharia capital market’s function as a tool for ethical investment and its macroeconomic impact in Indonesia. Drawing upon Islamic economic theory and qualitative document analysis, the research explores how instruments such as Sukuk and Sharia mutual funds facilitate religiously compliant investments and promote economic growth. Findings indicate that these instruments align with national development objectives by enhancing financial inclusion, capital formation, and infrastructure financing. The study also reveals that while the market offers stability and ethical transparency, structural challenges remain, including limited product diversity and secondary market depth. Policy recommendations include aligning Islamic finance with development planning, enhancing investor literacy, and diversifying financial instruments. The research contributes theoretically by integrating Islamic finance principles with endogenous growth and stakeholder theory. Practically, it provides guidance for optimizing the Sharia capital market’s role in sustainable economic development. The study positions Islamic finance as a viable mainstream strategy for inclusive growth in Indonesia.